Estrategias de intervención y posvención del comportamiento suicida - García Peña, John Jairo (Universidad Católica Luis Amigó, 2022)
This second book, framed in the research on suicidal behavior, contains strategies of intervention and postvention, both at the level of prevention and in the face of the occurrence of an event. It is the reflective result of a work, carried out for 4 years, funded by the Catholic University Luis Amigó, and carried out in eight localities of Antioquia in face-to-face and in some countries of the region in a virtual way; where technical advice and support has been provided in order to strengthen the institutional competences of these localities with regard to suicide; the book, presents this process of action research. We hope that its content will be useful for any person or institution interested in knowing how to deal with and contain this human problem.